2017
DOI: 10.1002/adma.201606576
|View full text |Cite
|
Sign up to set email alerts
|

MoS2–HgTe Quantum Dot Hybrid Photodetectors beyond 2 µm

Abstract: Mercury telluride (HgTe) colloidal quantum dots (CQDs) have been developed as promising materials for the short and mid-wave infrared photodetection applications because of their low cost, solution processing and size tunable absorption in the short wave-and midinfrared spectrum. However, the low mobility and poor photo-gain have limited the responsivity of HgTe CQDs-based photodetectors to only tens of mA/W. Here, we integrated HgTe CQDs on a TiO2 encapsulated MoS2 transistor channel to form hybrid phototrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
306
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(316 citation statements)
references
References 37 publications
10
306
0
Order By: Relevance
“…In the hybrid architectures, the TiO 2 layer between the HgTe QDs layer and the MoS 2 channel serves as an electronic receiving medium facilitating the electrons transfer to the MoS 2 and as a protective layer of the MoS 2 avoiding the effect from adsorbates such as oxygen and H 2 O in the air. In combination with the two points above, the hybrid device attained a prominent responsivity up to 10 6 A W −1 , a detectivity of 10 12 Jones, and a fast response on the order of milliseconds …”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 65%
See 1 more Smart Citation
“…In the hybrid architectures, the TiO 2 layer between the HgTe QDs layer and the MoS 2 channel serves as an electronic receiving medium facilitating the electrons transfer to the MoS 2 and as a protective layer of the MoS 2 avoiding the effect from adsorbates such as oxygen and H 2 O in the air. In combination with the two points above, the hybrid device attained a prominent responsivity up to 10 6 A W −1 , a detectivity of 10 12 Jones, and a fast response on the order of milliseconds …”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 65%
“…The remarkable performance benefited from the strong absorption of infrared light by PbS QDs and high carrier mobility of 20 cm 2 V −1 s −1 in the MoS 2 . More recently, Huo et al demonstrated a novel hybrid phototransistor operating beyond 2 µm light (Figure d), in which HgTe QDs were integrated on a TiO 2 covered few‐layer MoS 2 . Due to the high absorption of the HgTe QDs, a mass of photoinduced carriers are generated in the HgTe QDs, and the electrons can be transferred into the MoS 2 .…”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 99%
“…The material form options for light sensitizers can either be single crystals, thin films, heterojunctions, or even discrete quantum dots. [173,174] Due to the quantum confinement effect, the bandgap of CQDs can be continuously tuned by varying the QDs size, allowing MIR absorption ability with a wavelength longer than 3 µm for HgTe QDs, providing great potential for IR sensing of this kind of material despite the material's toxicity. Meanwhile, the selection of the bottom semiconductor can focus on large bandgap organic small molecules with high mobility and a large on/off ratio to enhance both the photoresponsivity and sensing dynamic range, or 2D-like organic single crystals to obtain an extremely low dark current.…”
Section: Hybrid Phototransistormentioning
confidence: 99%
“…In the recent years, HgTe has been widely used to explore devices with absorption above 2 μm . Pushing the nanocrystal absorption toward longer wavelength requires to update the device architecture.…”
Section: Discussionmentioning
confidence: 99%